Inovasi Pelatihan Guru Untuk Meningkatkan Pendidikan Inklusi Di Sekolah - Rega Fitriawati; Ida Rindaningsih (Insan Zenius Ilmiah, 2025)
Inclusive education emphasizes the importance of providing equal learning opportunities for all learners, including those with special needs. In its implementation, the success of inclusive education depends on the readiness and competence of teachers in dealing with the heterogeneity of students in the classroom. Innovative teacher training is one of the main strategies in responding to this challenge. Innovations in teacher training include developing training curricula based on real needs in the field, using educational technology to simulate inclusion cases, and collaborative training approaches between general and special education teachers. In addition, hands-on and reflective practice-based training models have proven effective in equipping teachers with applicable skills. This research shows that a structured and sustainable training program can improve teachers' understanding of inclusion principles, learning differentiation strategies and inclusive classroom management. Thus, innovations in teacher training not only improve professional competence but also create a supportive learning environment for all students. Therefore, it is necessary to support education policies that encourage the strengthening of teacher capacity through inclusive training that is relevant, contextual and adaptive to the times.